HR initiatives in building inclusive and accessible workplaces - Garg, Shalini (Emerald Publishing, 2020)
"Drawing upon empirical research from global multinational corporations comes a two-part reference book on how to develop resilient HR initiatives for building inclusive and accessible workplaces. Including a user-friendly training manual, this book equips you with a practical resource grounded in theory. The first part systematically reviews the existing literature to identify the gaps in current practices and discusses the results of the empirical research. Building on this, the second part reveals the training manual for guiding business leaders, academicians, practitioners, and students. By positioning business practices alongside cases, you can see the benefits and drawbacks of current HR initiatives. From race and religion, to LGBTQ, gender diversity and disability, the research covers a broad spectrum of issues facing modern workplaces and provides a fresh perspective on how to improve existing HR practices. Based on research from South Asia, this work provides hypothetical cases, action-oriented role plays, and creative exercises to reflect upon how we might address the global challenges of inclusion and accessibility."--Provided by publisher